2016
DOI: 10.1209/0295-5075/116/67002
|View full text |Cite
|
Sign up to set email alerts
|

Fully gapped superconducting state in Au 2 Pb: A natural candidate for topological superconductor

Abstract: -We measured the ultra-low-temperature specific heat and thermal conductivity of Au2Pb single crystal, a possible three-dimensional Dirac semimetal with a superconducting transition temperature Tc ≈ 1.05 K. The electronic specific heat can be fitted by a two-band s-wave model, which gives the gap amplitudes ∆1(0)/kBTc = 1.38 and ∆2(0)/kBTc = 5.25. From the thermal conductivity measurements, a negligible residual linear term κ0/T in zero field and a slow field dependence of κ0/T at low field are obtained. These… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Now, we compare our results with experimental works in doped DSM of Au 2 Pb [30][31][32][33][34] and Cd 3 As 2 [27][28][29] . Au 2 Pb shows superconductivity at T c ≈ 1.2K with D 2h symmetry at the ambient pressure 30,32,34 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Now, we compare our results with experimental works in doped DSM of Au 2 Pb [30][31][32][33][34] and Cd 3 As 2 [27][28][29] . Au 2 Pb shows superconductivity at T c ≈ 1.2K with D 2h symmetry at the ambient pressure 30,32,34 .…”
Section: Discussionmentioning
confidence: 85%
“…For both materials, the point-contact measurements reported that measured T c using a hard contact tip is much higher than the measured T c using a soft tip 27,29,32 . The point-contact measurements for Cd 3 As 2 showed the zero-bias conductance peak (ZBCP) and double conductance peaks symmetric around zero bias, which was interpreted as a signal of a topological Majorana surface superconductivity is reported in Cd 3 As 2 [27][28][29] and Au 2 Pb [30][31][32][33][34] . Both materials have Dirac points protected by TRS, IS, and C 4 rotational symmetry and share the tetragonal crystal system with D 4h point group symmetry.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…5 ). The experiments reported that the superconductivity is either conventional 33 , 34 or unconventional 32 depending on the physical situations. From our analysis, the superconducting phase of Pb is expected to be either a conventional fully gapped or unconventional topological mirror superconductor with a gapless SABS depending on physical parameters.…”
Section: Discussionmentioning
confidence: 99%